Case report: Fluoroscopic-assisted closed reduction and minimally invasive femoral capital physeal fracture repair in four calves - Loyd, Avery F.; Tatarniuk, Dane M.; Naiman, Jaron H.; Merkatoris, Paul T.; Troy, Jarrod R. (Frontiers in Veterinary Science, 2022)
Objective To describe a minimally invasive osteosynthesis (MIO) femoral capital physeal fracture (FCPF) repair technique using multiple smooth Steinmann pins in four calves. Study design Case series. Animal Four calves (< 60 days of age). Methods Medical records at a single referral hospital were searched for calves that had minimally invasive osteosynthesis (MIO) femoral capital physeal fracture (FCPF) repair performed using multiple Steinmann pins between 2020 and 2021. Calves receiving alternative repair, euthanasia without repair, or > 60 days of age were excluded. Medical records were reviewed together the following information: inciting FCPF cause, patient signalment, clinical sign duration pre-admission, history of dystocia, and any pre-admission treatment. Preoperative parameters collected included packed cell volume (PCV), serum total solids (TS), additional bloodwork when available, peripheral blood glucose, antimicrobial therapy, and analgesic medications. Preoperative coxofemoral radiographic images of all calves were obtained. Results/outcome Four calves were presented with severe hind limb lameness from varying etiologies. FCPF was diagnosed in all calves via radiograph. All FCPFs were repaired with an MIO repair technique using multiple Steinmann pins. Intraoperative fracture reduction and fixation were deemed appropriate by the attending surgeon with the use of fluoroscopy. Postoperatively, all calves retained normal weight bearing and were ambulating. One calf died postoperatively due to an unrelated comorbidity (severe bronchopneumonia and hyperkalemia). The three remaining calves survived to hospital discharge and were ambulating normally with an adequate range of motion at the time of discharge. Long-term follow-up reports were available for two cases, which revealed long-term survival at 210- and 146-days. Owners reported good ambulation, and one of the calves was placed in the show ring and was performing. However, one calf was lost to long-term follow-up. Conclusion MIO FCPF repair with multiple Steinmann pins, previously described in small animal species, can be implemented for FCPF repair in young calves. Clinical impact This case series provides a foundation for minimally invasive osteosynthesis technique translation to large animal juveniles and reports an alternative MIO technique for capital physeal closed fracture repair in calves.